2021
DOI: 10.15826/jtr.2021.7.2.095
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal policy and economic growth: Evidence from Central and Eastern Europe

Abstract: This study aims to estimate the impact of three fiscal instruments (direct tax revenue, indirect tax revenue and government consumption expenditure) on the economic growth of ten new European Union member states from Central and Eastern Europe– Bulgaria, Czechia, Estonia, Hungary, Latvia, Lithuania, Poland, Romania, Slovakia and Slovenia. We examine the hypothesis about the effect of expansionary fiscal policy on economic growth. The study employs a vector autoregression and annual Eurostat data for the period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
0
1
0
1
Order By: Relevance
“…This result is consistent with the findings of several studies (e.g., Blanchard & Perroti, 1999;Mukhtarov et al, 2018;Hamdi & Sbia, 2013;Ritcher et al 2015;Stoilova & Todorov, 2021;Ahmed, 2011), which argue that an increase in tax revenues leads to a reduction in GDP. However, in the aforementioned studies, taxes were raised leading to a reduction in GDP contrary to Uganda's case where tax reliefs provided to firms and households reduced its GDP.…”
Section: Impulse Response Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This result is consistent with the findings of several studies (e.g., Blanchard & Perroti, 1999;Mukhtarov et al, 2018;Hamdi & Sbia, 2013;Ritcher et al 2015;Stoilova & Todorov, 2021;Ahmed, 2011), which argue that an increase in tax revenues leads to a reduction in GDP. However, in the aforementioned studies, taxes were raised leading to a reduction in GDP contrary to Uganda's case where tax reliefs provided to firms and households reduced its GDP.…”
Section: Impulse Response Resultssupporting
confidence: 92%
“…Separately, many studies done in Europe and the USA (Ritcher et al, 2015;Stoilova & Todorov, 2021;Mukhtarov et al, 2018;Hamdi & Sbia, 2013) found a positive relationship between government spending and economic growth, and a negative link with taxes. However, Hamza and Milo (2021) used a VAR and found that total public expenditure significantly affects GDP.…”
Section: Empirical Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the expected reaction rate of GDP to the appearance of the sun. Stoilova & Todorov (2021) investigated the fiscal policy and growth and found that many costs have a direct influence on the tax rate and the show's aesthetic perception. In fact, I've come to realize that the entire concept is expanding.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Вопрос о том, могут ли изменения в фискальной политике повлиять на экономический рост, широко освещен в научной литературе [1][2][3][4][5][6]. Фискальная политика играет существенную роль в обеспечении экономического роста в стране [7,8].…”
Section: Introductionunclassified